lncRNA FENDRR Predicts Adverse Prognosis and Regulates the Development of Esophageal Squamous Cell Carcinoma Through Negatively Modulating miR-495-3p - Xue, Yangyang; Yang, Ran; Gong, Ping; Zhu, Hongjuan (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Esophageal squamous cell carcinoma (ESCC) is a major subtype of esophageal carcinoma and is highly prevalent in China. Identification of effective biomarkers could benefit ESCC management and therefore improve clinical outcomes. Evaluating the expression and significance of long non-coding RNA Fetal-lethal non-coding developmental regulatory RNA (FENDRR) in ESCC aims toprovide a biomarker candidate for ESCC. Materials and Methods: This study enrolled 117 ESCC patients and collected tissue samples. The expression of FENDRR in collected samples was analyzed by polymerase chain reaction. The Chi-square, Kaplan–Meier, and Cox analyses were performed to reveal its clinical value. In ESCC cells, FENDRR was regulated by cell transfection, and its effect on cell growth and motility was evaluated. Results: FENDRR was downregulated in ESCC and was associated with large tumor size, poor differentiation, late TNM stage, positive lymph node metastasis, and adverse development-free survival of ESCC patients. FENDRR acted as an adverse indicator for the prog nosis of ESCC patients. miR-495-3p was negatively regulated by FENDRR. Overexpressing FENDRR significantly suppressed ESCC cell growth and metastasis, while miR-495-3p reversed these effects. Conclusion: Downregulated FENDRR in ESCC predicted the malignant development and adverse prognosis of ESCC patients. FENDRR served as a tumor suppressor of ESCC by modulating miR-495-3p. Cite this article as: Xue Y, Yang R, Gong P, Zhu H. LncRNA FENDRR predicts adverse prognosis and regulates the development of esophageal squamous cell carcinoma through negatively modulating miR-495-3p. Turk J Gastroenterol. 2025;36(11):743-750.